A comparative study of market potential for logistics outsourcing in Estonia and Finland - Solakivi Tomi; Kiisler Ain; Hilmola Olli-Pekka (Emerald, 2022)
Purpose
This research analyzes the development of logistics outsourcing market in two countries, Estonia and Finland, with different paths as members of the single European market. The purpose of this paper is to examine whether the two markets have become more similar or whether their logistics costs and logistics markets have developed differently over time.
Design/methodology/approach
The development of the logistics market is addressed through two survey-based variables. Logistics costs are used to measure the size of the logistics market, whereas logistics outsourcing is analyzed to measure the development phase as well as the market potential for logistics service provision.
Findings
Estonian logistics outsourcing market was found to be underdeveloped and small compared to the Finnish market. At the same time, the logistics costs of Finnish companies are high and rising, whereas the costs of Estonian firms are declining.
Research limitations/implications
The results imply that the level of outsourcing might explain the visibility of logistics costs, which should be taken into account when making estimates on logistics costs both at the firm as well as on country level.
Social implications
Logistics sector is an important source of national competitiveness and employment. This research identifies subareas for the two countries on how to develop competitiveness through the logistics market.
Originality/value
This research provides a unique method to estimate the size of logistics outsourcing market in these two countries. It also represents as one of the rare works to provide multiyear comparison between countries in logistics costs.